Multiple Electrophysiological Evaluation of Carpal Tunnel Syndrome - Wu, XueYan; Su, Qiuju; Ding, Ping; Ji, Jie; Zhu, JiaYi (Journal of Brachial Plexus and Peripheral Nerve Injury, 2025)
To investigate a high-sensitivity electrodiagnostic (EDX) combination for diagnosing mild carpal tunnel syndrome (CTS).A total of 68 healthy controls (HCs, 136 hands) and 91 adult patients (CTSs, 162 hands) clinically diagnosed with CTS were enrolled. All patients accepted EDXs, including the sensory ganglia segment method of the median and ulnar nerves, and motor nerve conduction of the median and ulnar nerves. We examined the electrophysiological results and compared the sensitivity and specificity of various sensory nerve detection methods for the median nerve between the two groups.The electrophysiological results of the CTSs were significantly different from those of HCs. All EDX techniques selected showed high specificity (>96.3%), positive predictive value (>95.2%), and large area under the curve (0.922 as the smallest) for the diagnosis of CTSs. A comparison of the median distal sensory latencies with the ulnar distal sensory latencies in fingers 2 and 4 showed a high sensitivity of 98.1%. Comparison of the nerve conduction study between the median and ulnar nerves in the same hand is the most reliable EDX technique for diagnosing very mild CTS because of its high sensitivity and specificity.If clinical CTS patients exhibit normal median motor distal latency or sensory nerve conduction velocity across the wrist, a comparison of median and ulnar nerve conduction through the wrist, including M-U and M-U ringdiff, is recommended.
Keywords: carpal tunnel syndrome; electrodiagnostic; nerve conduction studies; median nerve; sensitivity